Practice of Community Social Environment Shared Ownership in Batutering Village, Sumbawa, West Nusa Tenggara - Wicaksono, Yudi Krisno; Maunah, Binti; Raman, Asrul (Strata Social and Humanities Studies, 2024)
This study examines the implementation of shared ownership of the social environment in Batutering Village, Sumbawa, West Nusa Tenggara, Indonesia. It focuses on how the community's management of communal resources can strengthen collective consciousness and improve the quality of life. Qualitative methods, including in-depth interviews and participant observation, are used to understand social dynamics and their impact on the environment. Findings indicate that communal activities, such as community service and other social activities, not only help maintain the environment but also strengthen social bonds and support shared well-being. These results suggest that a sense of belonging and cooperation within the community play an important role in creating a healthier and more harmonious environment. This study reinforces the notion that residents actively participating in the management of their local resources can yield significant social and environmental benefits, underscoring the significance of education and communal collaboration in sustainability initiatives. This study provides valuable insights for developing more inclusive and effective shared ownership models in other communities.